Desenvolvimento e caracterização físico-química, sensorial e aspectos nutricionais de granolas isentas de glúten, contendo Chenopodium quinoa, BRS Piabiru, Amaranthus cruentus, BRS Alegria e Linum usitiasimum, L - Souza, Aloisio Henrique Pereira de (2011)
INTRODUCTION. Celiac disease is the intolerance to gluten proteins intake and the treatment is based on restricting the consumption of foods containing prolamins. The availability and variety of gluten-free products are lower than foods that contain gluten. Due to the presence of essential amino acids and fatty acids, amaranth (Amaranthus spp.), Quinoa (Chenopodium quinoa Willd) and flax (Linum usitatissimum L.) are promising ingredients for formulation of these products. Cultivars C. Quinoa, BRS Piabiru and A. cruentus, BRS Alegria were obtained through genetic improvement carried out by EMBRAPA - Cerrados intending to remove the saponins, to increase productivity and to maintain the chemical composition. Granola is a product consisting of the mixture of dried fruits, grains and oilseeds. It is considered a nutritive food, source of fiber, carbohydrates and lipids. The development of foods that contain minerals, fiber, fatty acids and essential amino acids, without anti-nutritional factors, are required mainly in dietary restrictions, such as the case of celiac disease. AIMS. The purpose of this work was the formulation of gluten-free granola, with C. quinoa, BRS Piabiru and A. cruentus, BRS Alegria as source of essential amino acids and minerals, and L. usitiassimum L. as source of alpha-linolenic acid. Physico-chemical characteristics were analyzed, such as sensory and nutritional aspects. MATERIALS AND METHODS. Three formulations of gluten-free granola containing amaranth, quinoa and flaxseed were developed. For the processing of granola, it was obtained pseudocereals from EMBRAPA - Cerrados, flax and other ingredients used are in the trade of the city of Maringa-PR. The sample consisted of the homogenisation of 60 kg of grains and subsequent application of the quartering method. The processing of the formulations was based on binder phase production (syrup) and solid phase (grains, nuts and raisins), and the ingredients for the formation of binder and solid phases, respectively, were mixed and cooked in a conventional oven in 200ºC for 30 minutes. The following analysis were performed: presence of gluten by ELISA (Enzyme-linked immunosorbent assay), moisture, ash, crude protein, crude fiber and carbohydrates, calculated and crude energy, water activity, color and texture, composition of fatty acids and minerals, Bacillus cereus, coliforms at 45ºC, coagulase-positive staphylococcus and Salmonella sp.; sensory tests of acceptability through the attributes: appearance, flavor, texture, crispness, overall acceptance, order of preference and purchase intent, with 80 consumers. The dietary reference intakes (DRI) was calculated with percentage estimate of dietary contribution of strictly minerals: calcium, copper, iron, manganese, magnesium and zinc, for age groups and sex. RESULTS AND DISCUSSION. It was possible to develop formulations of gluten-free granola, because this substance was not detected in the analyzed samples. For the proximal composition, there was difference (p<0.05) of moisture, ash and protein. The use of promising sources of protein is required, because in general, the flour used in processing products for celiacs have a high concentration of carbohydrates and low protein content. There was no difference in total lipids content between the formulations. The direct calorimetry provided more accurate data than the indirect method. The color parameters showed faint brightness, less intense of red and dark yellow, varying in color to brown. In the composition of fatty acids there was a high amount of oleic and linoleic acids, which is due to the presence in the grains and nuts used in processing. Levels below 2% were found to saturated fatty acid in granola and the ratio between polyunsaturated and saturated was approximately 2:1. Among the polyunsaturated fatty acids, the alpha-linoleic and linolenic acids are very important because they are considered strictly essential. In the mineral composition, the majority was the mineral calcium, which contributes to the bioavailability and absorption of magnesium, manganese and zinc. The sanitary conditions were satisfactory due to the absence of micro-organisms analyzed and low water activity. For the sensory analysis of the products, the attributes ranged from liked slightly to liked moderately and showed good acceptance, there was no preference and high purchase intent. The granola reached values above 10% of DRI for strictly essential trace elements. CONCLUSIONS. The use of foods naturally gluten-free granola allowed the development of this kind of product for celiac individuals. The selection of promising materials as quinoa, amaranth and flax contributed to increase the levels of proteins, lipids and minerals in the products. The levels of saturated fatty acids were below 2% and the ratio between polyunsaturated and saturated was appropriate, and n-6/n-3 ratio of the formulation was in accordance with the recommendations in other studies. The minerals reached values above 10% of DRI. The formulation C had the best contribution on the content of lpha-linolenic acid in the portion and granola can be considered as source of copper, iron, manganese and zinc. The products presented good sanitary conditions and had a good acceptance for the attributes studied, there was no preference of formulation and all showed high levels of purchase intent.